TRIM33 drives prostate tumor growth by stabilizing androgen receptor from Skp2‐mediated degradation. (4th July 2022) - Chen, Mi; Lingadahalli, Shreyas; Narwade, Nitin; Lei, Kate Man Kei; Liu, Shanshan; Zhao, Zuxianglan; Zheng, Yimin; Lu, Qian; Tang, Alexander Hin Ning; Poon, Terence Chuen Wai; Cheung, Edwin
Abstract: Androgen receptor (AR) is a master transcription factor that drives prostate cancer (PCa) development and progression. Alterations in the expression or activity of AR coregulators significantly impact the outcome of the disease. Using a proteomics approach, we identified the tripartite motif‐containing 33 (TRIM33) as a novel transcriptional coactivator of AR. We demonstrate that TRIM33 facilitates AR chromatin binding to directly regulate a transcription program that promotes PCa progression. TRIM33 further stabilizes AR by protecting it from Skp2‐mediated ubiquitination and proteasomal degradation. We also show that TRIM33 is essential for PCa tumor growth by avoiding cell‐cycle arrest and apoptosis, and TRIM33 knockdown sensitizes PCa cells to AR antagonists. In clinical analyses, we find TRIM33 upregulated in multiple PCa patient cohorts. Finally, we uncover an AR‐TRIM33‐coactivated gene signature highly expressed in PCa tumors and predict disease recurrence. Overall, our results reveal that TRIM33 is an oncogenic AR coactivator in PCa and a potential therapeutic target for PCa treatment. Synopsis: TRIM33 is an oncogenic coactivator of AR‐dependent transcription in prostate cancer. TRIM33 exerts its coactivator activity by stabilizing AR from Skp2‐mediated ubiquitination and proteasomal degradation. TRIM33 coactivates AR‐mediated transcription in prostate cancer (PCa) by stabilizing AR from Skp2‐mediated ubiquitination and proteasomal degradation. TRIM33 is highly expressed in PCa tumors and is required for prostate tumor growth. TRIM33 and AR target genes define an AR‐TRIM33‐coactivated gene signature that is highly expressed in PCa tumors. Patients with a high expression of this gene signature show a higher risk of disease recurrence. Abstract : TRIM33 is an oncogenic coactivator of AR‐dependent transcription in prostate cancer. TRIM33 exerts its coactivator activity by stabilizing AR from Skp2‐mediated ubiquitination and proteasomal degradation.